Food contact materials rubbers, silicones, coatings and inks - Forrest, Martin J. (ISmithers, 2009)
This book is an amalgamation of data from four recent projects. This report provides a wealth of information taken from the results and findings of research projects on: Migration Data of Food Contact Rubbers (Two projects), Rubber Breakdown Products, Chemical Migration from Silicones used in Connection with Food Contact Materials and Articles and An Assessment of the Potential of Migration of Substances from Inks and their Respective Coatings. Each review provides an expert overview of the products as food contact materials, with a comprehensive accompanying list of relevant references from th.
Keywords: Food contamination.; Food -- Packaging.; elektronické knihy; electronic books